Effects of Raga music and Chinese five-element on milk production, antioxidant, neuroendocrine, immune, and welfare indicators in dairy cows - Cao, Zongjing; Zhao, Huiqiu; Feng, Zhihua; Yang, Bowen; Li, Zhijia; Ma, Xiuguo; Gu, Sukun; Ma, Ning (Frontiers in Veterinary Science, 2025)
In recent years, increasing attention has been paid to the effects of music on animal productivity. However, research specifically examining music’s impact on dairy cows remains limited, with existing studies reporting inconsistent findings. This study investigated the effects of Raga music and Chinese Five-Element music on production performance, stress response, neuroendocrine function, immune system, and welfare indicators in lactating dairy cows. Sixty healthy lactating Holstein cows with similar parity were randomly divided into three treatment groups, with 20 replicates in each group. The experiment involved three feeding environments (no music/classical music/traditional Chinese five-element music) and lasted for 60 days. Results showed that compared with the control group, dairy cows receiving music therapy exhibited a significant increase in average daily milk yield (p < 0.001). Both music intervention treatments had lower feed-to-milk ratios than the control group, with the Raga music treatment demonstrating the lowest ratio (p > 0.05). Dairy cows in the music intervention groups displayed significant improvements in serum biochemical parameters, characterized by decreased levels of alanine aminotransferase (ALT) and triglycerides (TG) (p < 0.05), and increased concentrations of glucose (GLU) and serum albumin (ALB) (p < 0.05). In antioxidant indices, enhanced glutathione peroxidase (GSH-PX) activity (p < 0.001) and reduced malondialdehyde (MDA) levels (p < 0.001) were observed. Notably, music intervention significantly increased serum concentrations of immunoglobulins G (IgG), M (IgM), and A (IgA) (p < 0.05), suggesting its potential role in enhancing immune function in dairy cows. Dairy cows exposed to Raga music showed significant neuroendocrine and behavioral changes, with decreased levels of glutamate (Glu) and cortisol (COR) (p < 0.05), and increased concentrations of growth hormone (GH), 5-hydroxytryptamine (5-HT), β-endorphin (β-EP), substance P (SP), and γ-aminobutyric acid (GABA) (p < 0.05). Behaviorally, cows in the experimental groups exhibited reduced physical activity (p < 0.05) but increased rumination and lying time (p > 0.05), indicating improved relaxation and metabolic efficiency. In conclusion, the comprehensive assessment demonstrates that music intervention significantly enhances milk production, antioxidant capacity, immune function, and overall welfare in dairy cows. Among the interventions, Raga music exhibits the most pronounced effects, particularly in achieving a lower feed-to-milk ratio.